2021
DOI: 10.1017/s0033291721000659
|View full text |Cite
|
Sign up to set email alerts
|

The role of characterisation in everyday voice engagement and AVATAR therapy dialogue

Abstract: Background Voices are commonly experienced as communication with a personified ‘other’ with ascribed attitudes, intentionality and personality (their own ‘character’). Phenomenological work exploring voice characterisation informs a new wave of relational therapies. To date, no study has investigated the role of characterisation in behavioural engagement with voices or within psychological therapy for distressing voices. Methods Baseline characterisation (the degree to which the voice is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 38 publications
2
17
0
Order By: Relevance
“…Voice‐hearers might benefit from AVATAR therapy primarily because of the opportunity to habituate to, and assert their needs to a persecutory voice under the guidance of a well‐attuned therapeutic relationship, or it could be that specific therapeutic actions, such as unfolding relational and developmental understanding of voices during the dialogue, are fundamental to address distress. A new trial (http://www.isrctn.com/ISRCTN55682735) is planned to examine this question and explore moderators of treatment efficacy, such as complexity of characterization of the dominant voice, which we already know is associated with engagement in voice dialogue (Ward et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Voice‐hearers might benefit from AVATAR therapy primarily because of the opportunity to habituate to, and assert their needs to a persecutory voice under the guidance of a well‐attuned therapeutic relationship, or it could be that specific therapeutic actions, such as unfolding relational and developmental understanding of voices during the dialogue, are fundamental to address distress. A new trial (http://www.isrctn.com/ISRCTN55682735) is planned to examine this question and explore moderators of treatment efficacy, such as complexity of characterization of the dominant voice, which we already know is associated with engagement in voice dialogue (Ward et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, virtual reality therapies have been recommended to treat various psychiatric disorders, including schizophrenia spectrum disorders (Bisso et al 2020). The Avatar therapy model, which can be categorized within virtual reality therapies, is also a novel therapy model in which interpersonal relationship-based psychotherapeutic processes are implemented (Ward et al 2022).…”
Section: Past Present and Future Of Schizophrenia Treatmentmentioning
confidence: 99%
“…In addition to the widespread use of virtual reality technologies in the treatment of anxiety, fear, and phobia, it is also known that they are used in the treatment of other mental disorders such as eating disorders, obsessive-compulsive disorder, and schizophrenia (Vardarlı 2021). The avatar therapy model is a virtual reality therapy model based on interpersonal relationships and designed to make sense of the mechanism of auditory hallucinations in a person's life (Ward et al 2022). Virtual reality therapies, among other new-world technologies, are likely to be preferred in the coming years over costly treatment options for treating mental disorders that are difficult to understand using traditional therapy models.…”
Section: Virtual Reality Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…voices with ascribed attitudes, intentionality, and personality (their own 'character'). Ward and colleagues [21] found that one third of individuals in their AVAT AR therapy sample reported a highly characterised dominant voice (e.g. voices associated with a family member or identifiable 'stranger' with a consistent background and personality).…”
Section: Background and Rationale {6a}mentioning
confidence: 99%